PENGARUH KATALIS TEMBAGA DAN KROM TERHADAP EMISI GAS CARBON MONOKSIDA DAN HIDRO CARBON PADA KENDARAAN MOTOR BENSIN - RM. Bagus Irawan (TRAKSI, 2006)
The aims of this experiment are firstly to coducted a catalytic converter secondly, to find out to what extend Copeer and Crom ( CuCr ) as catalyst is effecient. To measure the concentration of Carbon Monoxide and Hidro Carbon on frame there are two conditions required. First is when the engine is on, and second is when CuCr catalytic converter is applied using gas analyzer. This experiment results in the fact that the use of CuCr catalytic convertyer with the varian number of its cell reduces the production of Carbon Monoxide and Hidro Carbon of premium automobile   Kata kunci : Catalytic Converter, Katalis CuCr, Konsentrasi CO dan  HC